Experimental treatment with sodium stibogluconate of hamsters infected with Leishmania (Leishmania) chagasi and Leishmania (Leishmania) amazonensis - Elizabeth M. de Figueiredo; Jaime Costa e Silva; Reginaldo P. Brazil (Sociedade Brasileira de Medicina Tropical (SBMT), 1999)
The present paper reports the experimental treatment of hamsters infected with Leishmania chagasi and Leishmania amazonensis with sodium stibogluconate (20mg/kg/day x 20 days). Only with L. chagasi did the treatment result in the complete elimination of parasites from the spleen. However, no parasitological cure was achieved in hamsters infected with L. amazonensis.